2005
DOI: 10.1186/1477-7827-3-28
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in female reproduction

Abstract: In a healthy body, ROS (reactive oxygen species) and antioxidants remain in balance. When the balance is disrupted towards an overabundance of ROS, oxidative stress (OS) occurs. OS influences the entire reproductive lifespan of a woman and even thereafter (i.e. menopause). OS results from an imbalance between prooxidants (free radical species) and the body's scavenging ability (antioxidants). ROS are a double-edged sword -they serve as key signal molecules in physiological processes but also have a role in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
551
1
22

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,218 publications
(587 citation statements)
references
References 206 publications
(284 reference statements)
13
551
1
22
Order By: Relevance
“…30 However, several inevitable deleterious metabolites or damage stresses, including reactive oxide species (ROS) and DNA damage, will lead to adverse impact on embryo development and pregnancy. 31 SOD activity assay confirmed that the antioxidant system was boosted in decidual cells during in vivo and in vitro decidualization (Fig. 11A, B).…”
Section: E2f8 Mediates Endoreplication and Polyploidization By Transcmentioning
confidence: 71%
“…30 However, several inevitable deleterious metabolites or damage stresses, including reactive oxide species (ROS) and DNA damage, will lead to adverse impact on embryo development and pregnancy. 31 SOD activity assay confirmed that the antioxidant system was boosted in decidual cells during in vivo and in vitro decidualization (Fig. 11A, B).…”
Section: E2f8 Mediates Endoreplication and Polyploidization By Transcmentioning
confidence: 71%
“…In Drosophila, lack of Cu-Zn SOD also causes nearly complete sterility in males (12). A growing body of evidence associates ROS in humans with reduced sperm vitality (13), ovarian DNA damage (14), and preeclampsia and other pregnancy complications (15). Surprisingly, mice in which the catalase gene is disrupted grow normally and are as fertile as wild-type mice (16), indicating that, in vertebrates, this enzyme is not essential to protect spermatozoids or the ovaries from oxidative damage.…”
Section: •ϫmentioning
confidence: 99%
“…High ROS levels may also cause adverse pregnancy outcomes or embryonic/fetal losses [120][121][122] and are implicated in the etiopathogenesis of cystic ovarian disease [123]. ROS and the oxidative stress index in cows may be higher in the luteal phase than follicular phase, especially when progesterone is high.…”
Section: Relationship Between Progesterone and Oxidative Stress In Rumentioning
confidence: 99%